Beta-adrenoblockers: treatment principles in international clinical guidelines - S. Yu. Martsevich (Кардиоваскулярная терапия и профилактика)
The article contains data on beta-blocker efficacy in cardiology – the results of large, randomized clinical trials, and evidence-based clinical guidelines on beta-blocker therapy.